Expression of Love Emotions in the Audiovisual Field - Kerevičienė, Jurgita; Grikietis, Livija (Respectus Philologicus, 2018)
Audiovisual work is significant in its narrative and created images. Conveyance, recognition and experiences of characters’ emotions are not disregarded. By using the most elaborated audio and visual means, filmmakers try not only to involve the viewers in the film plot but also encourage them to discover characters’ emotions and feelings, go through their experiences and perceive their emotional transformation. This article aims at revealing the conceptualisation of transformation of characters’ love emotions in the film “Pleasantville”. Cognitive metaphor and metonymy theories as well as the identified multimodal meaning making resources indicating the embodiment of prevailing love emotions are applied in the analysis. Firstly, emotions, their notion, typology and somatic aspects of love emotions are discussed. Then the focus is put on multimodal constructions and their audiovisual expression. The empirical part of the article deals with the analysis of the most intense love emotions discerned in the film, namely, ecstasy and admiration, paying the primary attention to the multimodal modes used to reveal their conceptualisation.
Keywords: Multimodal Metaphor; Multimodal Modes; Audiovisual Expression; Conceptualisation of Emotions.